ENT 530 Social Media Portfolio: Storebagmy / Muhammad Nur Hazreen Nizamuddin - Nizamuddin, Muhammad Nur Hazreen (2020)
Storebagmy is a dropship business that sell handbag from United States outlet and the Facebook page post has successfully achieved the goals to post copywriting 6 teasers, 16 soft sells, 16 hard sells. The copywriting post started from November till end of December. The business is started from March 2019 and the business already sold the bag more than 100 of units. There are a lot of good and positive feedback from the customers that buy from Storebagmy. Customers satisfied with the services and they gain confidence to buy from Storebagmy because of the feedback from previous customer and the video that Storebagmy provide is convincing. The product that Storebagmy sell also have a constant demand in the market and it provide a good insight for the continuation of sale to our customers. The bag was sold average 5 bag per month and they way we attract our customers by providing a good video and pictures to gain their trusts. To find a new customer Storebagmy use digital marketing which is the Facebook Advertisement. The advertisement spend is RM30 per day and usually Storebagmy will run the advertisement by end of month and early of month only. Therefore, by constantly post a content and run the advertisement the business can grow more and maintain the sales every month.